I want to stay and excel: a field theory perspective on the career development of male nurses - Qinyang Wu; Shihai Xu; Yanxia Wu; Hualong Ma; Yingying Cheng; Peng Liu; Yishang Zhuo; Zihan Li; Ni Gong; Qiaohong Yang (BMC Nursing)
Abstract Background The stable development of male nurses could potentially help address the nursing shortage. However, their career trajectories are polarized: while some male nurses exit the profession, others excel and become distinguished practitioners. Understanding the internal processes and needs of male nurses is essential for supporting their continuous career development. Objective This qualitative study aimed to elucidate the career development paths of male nurses after their entry into the profession. Methods This study is a descriptive qualitative study. Face-to-face semi-structured in-depth interviews were conducted with fourteen male nurses from five tertiary hospitals in Guangdong Province between July 23 and October 20, 2023, and data were analyzed using Colaizzi’s 7-step analysis. The study is not registered. Results Drawing on Pierre Bourdieu’s “field theory,” three main themes and nine sub-themes were identified to outline the career development pathways of male nurses. The themes are “Capital Accumulation: Establishing a Foothold” (Positive Exchange of Capital; Special Capital of Minorities); “Field-Habitual Conflict and Adjustment: From Livelihood to Value” (Considering Leaving: Surviving Under Pressure; Staying Reluctantly: Choosing Stability; Deciding to Stay: Commitment Through Experience; Striving for Excellence: Building Professional Confidence); “Field Constraints: Potential for accelerated progress remained unrealized” (Lack of Guiding Lights, Insufficient Research Training, Unclear Career Planning). Conclusions This study highlights male nurses’ career progression through capital accumulation and evolving professional identity: from initial turnover intentions to achieving excellence. Recognizing gender-specific challenges and fostering professional growth may improve confidence, team stability, and organizational outcomes.